Best practices for online team‐based learning: Strengthening teams through formative peer evaluation. (16th June 2021) - Brown, Tom; Rongerude, Jane; Leonard, Bruce; Merrick, Laura C.
Abstract: This chapter describes best practices for the peer evaluation process in online team‐based learning (TBL). Formative peer evaluation is an essential element of effective course delivery for online TBL classes, and when done well, shapes a group of individuals with a shared set of tasks into an interdependent team of learners. More generally, emphasizing the formative over the summative aspects of peer evaluation supports the development of the soft skills and behaviors students require to become more adaptive, resilient, reflective, and collaborative human beings.